Using consented health record linkage in a longitudinal cohort study. (2017) - Tingay, Karen; Akbari, Ashley; Bandyopadhyay, Amrita; Bedford, Helen; Brophy, Sinead; Borja, Mario Cortina; Fitzsimons, Emla; Griffiths, Lucy; Healy, Melanie; Johnson, Jon; Setakis, Efrosini; Walton, Suzanne; et al.
No abstract available